Evaluation of Clinical Characteristics and Outcomes of Obstetric Patients Admitted to Intensive Care Unit: A case control study - Shrestha, Deepak; Aryal, Shreyashi; Baniya, Sebina (Journal of Lumbini Medical College, 2018)
Introduction: The need for critical care support and admission to intensive care unit (ICU) in obstetric population is infrequent. The proportion ranges from 0.1 to 8.5%. Yet, obstetric admissions to ICU and mortality continue to have a significant impact on overall maternal health care. The study of epidemiology and predictors of obstetric admissions to ICU will prove a useful proxy for better understanding maternal near miss events and mortality. Methods: This was a case control study reviewing all the obstetric cases admitted to ICU over a study period of five years. The individual files were recovered from the record section and data pertaining to referral status, demographics, clinical profile and ICU information were retrieved. The ICU data comprised of the length of ICU stay, indications for admission, interventions required, and outcomes. The data were then compared to historical controls. Results: A total of 80 patients were admitted to ICU accounting for 0.84% of total deliveries and 4.6% of total ICU admissions. Mean age was 24.84 years, mean gestational age was 32.33 weeks, and mean blood loss was 707.27 ml. Hypertensive disorder of pregnancy followed by obstetric hemorrhage were the most common indications. Lower gestational age, increased blood loss, emergency cesarean sections, and surgical interventions were noteworthy risk factors for ICU admissions. There was a mortality rate of 5%. Conclusion: Hypertensive disorders account for the most number of admissions to ICU followed by obstetric hemorrhage. Lower gestational age, increased blood loss and emergency cesarean section are notable risk factors for ICU admission. DOI: https://doi.org/10.22502/jlmc.v6i1.167